Güzel sanatlar liseleri bazında çağdaş resim sanatında beden kullanımının estetik açıdan incelenmesi - Koçyiğit, Hümeyra (My University, 2019)
Bu araştırmada Güzel Sanatlar Liselerinin müfredat programları doğrultusunda; Güzel Sanatlar Liseleri Bazında Çağdaş Resim Sanatında Beden Kullanımının Estetik Açıdan İncelenmesi ve beden kullanımına estetik açıdan müfredat programlarında ne kadar yer verildiğinin araştırılması amaçlanmaktadır.Doküman analizi tekniği kullanılarak yapılan bu araştırmada aşağıdaki sorulara cevap aranmıştır: 1. Güzel Sanatlar Liselerinin müfredatlarında estetiğin yeri nedir?2. Estetik derslerinde, Çağdaş Sanatın yeri nedir?3. Estetik derslerinde, beden kullanımının yeri nedir?4. Güzel Sanatlar Liseleri müfredatında “Beden” konusu yer almakta mıdır? 5. Güzel Sanatlar Liseleri “ Estetik” dersinde kazandırılması gereken olgular nelerdir? 6. Güzel Sanatlar Liseleri “ Estetik” dersinde kullanılan yöntem ve teknikler nelerdir? 7. Güzel Sanatlar Liseleri müfredatında Çağdaş Resim Sanatında Estetik konusuna ayrılan süre nedir? Araştırmanın veri toplama araçları; her türlü birincil ve ikincil kaynaklardan, kitaplar, tezler, makaleler, internet kaynakları, dergiler kullanılarak ulusal ve uluslararası araştırmalar ve Güzel Sanatlar Lisesi müfredat programlarıdır. Yabancı dildeki kaynaklar çevrilmiş ve araştırmaya dahil edilmiştir.Araştırmada nitel araştırma yöntemlerinden doküman analizi tekniği kullanılmış ve elde edilen veriler yorumlanmıştır. Estetik dersi müfredat programından yola çıkılarak kazanımlar, öğrenme alanları ve öğrenme düzeyleri tablo haline getirilmiştir. Buradan elde edilen bilgiler çağdaş sanatta bedenini kullanan sanatçı yapıtlarıyla ilişkilendirilmiş, yapıtların bilişsel, duyuşsal ve psikomotor alanlara katkısı tartışılmıştır. Araştırmada elde edilen bulgular aşağıdaki gibidir;Güzel Sanatlar Liselerinde icra edilen estetik derslerinin, sanata anlam, içerik, değer ve tarihilik gibi anlamlar katması nedeniyle estetik dersi önem taşımaktadır. Öğrencilerin edindikleri bilgiler doğrultusunda eleştirebilen, sorgulayabilen, sanatı koruyabilen, geçmiş ve gelecek arasında bağ kurabilen bir sanat üreticisi ve tüketicisi yetiştirilmesi amaçlanmaktadır. Tüm bunlara ise Güzel Sanatlar Liseleri Estetik dersinde çağdaş sanat konusuna yeterince yer verilerek kazanılabileceği düşünülmektedir. Araştırmada müfredat programından edinilen bulgulara göre teknik olarak; soru cevap tekniği, yöntem olarak; problem çözme ve tartışma yöntemi kullanıldığı görülmüştür. Sonuç olarak; çağdaş Sanatta Estetiğin incelenerek eğitim açısından önemi vurgulanmıştır.Estetik, Çağdaş Sanat, Beden, Sanat Eğitimi

In this study, according to the curriculum of Fine Arts High Schools; The aim of this course is to investigate the usage of body in aesthetics and the use of body in aesthetic terms in the curriculum of contemporary art.In this research which was conducted by using document analysis technique, the following questions were sought:1.What is the place of aesthetics in the curricula of Fine Arts High Schools?2.What is the place of contemporary art in aesthetics?3.What is the place of body use in aesthetics?4.Does the subject of “Body” take place in the Fine Arts High School curriculum?5.What are the facts that need to be given in Fine Arts High Schools aesthetic lessons?6.What are the methods and tecniques used in fine arts high schools aesthetics lessons?7. What is the time devoted to the subject of Aesthetics in Contemporary Art in the curriculum of Fine Arts High Schools?The data collection tools that were used in this research ; all kinds of primary and secondary sources, books, theses, articles, internet resources, journals, national and international research and Fine Arts High School curriculum. Foreign language sources have been translated and included in the research. In the research, document analysis technique which is one of the qualitative research methods was used and the obtained results were interpreted. Aesthetic course is based on the curriculum . Gains, learning areas and learning levels are tabulated. The information obtained here is associated with the works of artists using their body in contemporary art, the contribution of the works to cognitive, affective and psychomotor fields is discussed.The findings obtained in this study are as follows: Because of atributing a meaning content and history to the art, aesthetic are important while performing courses in Fine Arts High Schools . The aim of this course is to educate an art producer and consumer who can criticize, question, and protect the art and connect the past and the future. It’ s thought to be reached by placing contemporary art sufficiently in aesthetic lessons in Fine Arts High Schools. The use of the body improves creativity in man and goes beyond the traditional understanding of art and provides an interdisciplinary gain. According to the findings of the curriculum in the study, as a technical; question-answer technique, as a method; problem solving and discussion method was used.As a result; The importance of aesthetics in contemporary art is examined.Key Words: Aesthetic, Contemporary Art, Body, Art EducationIn this study, according to the curriculum of Fine Arts High Schools; The aim of this course is to investigate the usage of body in aesthetics and the use of body in aesthetic terms in the curriculum of contemporary art.In this research which was conducted by using document analysis technique, the following questions were sought:1.What is the place of aesthetics in the curricula of Fine Arts High Schools?2.What is the place of contemporary art in aesthetics?3.What is the place of body use in aesthetics?4.Does the subject of “Body” take place in the Fine Arts High School curriculum?5.What are the facts that need to be given in Fine Arts High Schools aesthetic lessons?6.What are the methods and tecniques used in fine arts high schools aesthetics lessons?7. What is the time devoted to the subject of Aesthetics in Contemporary Art in the curriculum of Fine Arts High Schools?The data collection tools that were used in this research ; all kinds of primary and secondary sources, books, theses, articles, internet resources, journals, national and international research and Fine Arts High School curriculum. Foreign language sources have been translated and included in the research. In the research, document analysis technique which is one of the qualitative research methods was used and the obtained results were interpreted. Aesthetic course is based on the curriculum . Gains, learning areas and learning levels are tabulated. The information obtained here is associated with the works of artists using their body in contemporary art, the contribution of the works to cognitive, affective and psychomotor fields is discussed.The findings obtained in this study are as follows: Because of atributing a meaning content and history to the art, aesthetic are important while performing courses in Fine Arts High Schools . The aim of this course is to educate an art producer and consumer who can criticize, question, and protect the art and connect the past and the future. It’ s thought to be reached by placing contemporary art sufficiently in aesthetic lessons in Fine Arts High Schools. The use of the body improves creativity in man and goes beyond the traditional understanding of art and provides an interdisciplinary gain. According to the findings of the curriculum in the study, as a technical; question-answer technique, as a method; problem solving and discussion method was used.As a result; The importance of aesthetics in contemporary art is examined.Key Words: Aesthetic, Contemporary Art, Body, Art EducationIn this study, according to the curriculum of Fine Arts High Schools; The aim of this course is to investigate the usage of body in aesthetics and the use of body in aesthetic terms in the curriculum of contemporary art.In this research which was conducted by using document analysis technique, the following questions were sought:1.What is the place of aesthetics in the curricula of Fine Arts High Schools?2.What is the place of contemporary art in aesthetics?3.What is the place of body use in aesthetics?4.Does the subject of “Body” take place in the Fine Arts High School curriculum?5.What are the facts that need to be given in Fine Arts High Schools aesthetic lessons?6.What are the methods and tecniques used in fine arts high schools aesthetics lessons?7. What is the time devoted to the subject of Aesthetics in Contemporary Art in the curriculum of Fine Arts High Schools?The data collection tools that were used in this research ; all kinds of primary and secondary sources, books, theses, articles, internet resources, journals, national and international research and Fine Arts High School curriculum. Foreign language sources have been translated and included in the research. In the research, document analysis technique which is one of the qualitative research methods was used and the obtained results were interpreted. Aesthetic course is based on the curriculum . Gains, learning areas and learning levels are tabulated. The information obtained here is associated with the works of artists using their body in contemporary art, the contribution of the works to cognitive, affective and psychomotor fields is discussed.The findings obtained in this study are as follows: Because of atributing a meaning content and history to the art, aesthetic are important while performing courses in Fine Arts High Schools . The aim of this course is to educate an art producer and consumer who can criticize, question, and protect the art and connect the past and the future. It’ s thought to be reached by placing contemporary art sufficiently in aesthetic lessons in Fine Arts High Schools. The use of the body improves creativity in man and goes beyond the traditional understanding of art and provides an interdisciplinary gain. According to the findings of the curriculum in the study, as a technical; question-answer technique, as a method; problem solving and discussion method was used.As a result; The importance of aesthetics in contemporary art is examined.Key Words: Aesthetic, Contemporary Art, Body, Art EducationIn this study, according to the curriculum of Fine Arts High Schools; The aim of this course is to investigate the usage of body in aesthetics and the use of body in aesthetic terms in the curriculum of contemporary art.In this research which was conducted by using document analysis technique, the following questions were sought:1.What is the place of aesthetics in the curricula of Fine Arts High Schools?2.What is the place of contemporary art in aesthetics?3.What is the place of body use in aesthetics?4.Does the subject of “Body” take place in the Fine Arts High School curriculum?5.What are the facts that need to be given in Fine Arts High Schools aesthetic lessons?6.What are the methods and tecniques used in fine arts high schools aesthetics lessons?7. What is the time devoted to the subject of Aesthetics in Contemporary Art in the curriculum of Fine Arts High Schools?The data collection tools that were used in this research ; all kinds of primary and secondary sources, books, theses, articles, internet resources, journals, national and international research and Fine Arts High School curriculum. Foreign language sources have been translated and included in the research. In the research, document analysis technique which is one of the qualitative research methods was used and the obtained results were interpreted. Aesthetic course is based on the curriculum . Gains, learning areas and learning levels are tabulated. The information obtained here is associated with the works of artists using their body in contemporary art, the contribution of the works to cognitive, affective and psychomotor fields is discussed.The findings obtained in this study are as follows: Because of atributing a meaning content and history to the art, aesthetic are important while performing courses in Fine Arts High Schools . The aim of this course is to educate an art producer and consumer who can criticize, question, and protect the art and connect the past and the future. It’ s thought to be reached by placing contemporary art sufficiently in aesthetic lessons in Fine Arts High Schools. The use of the body improves creativity in man and goes beyond the traditional understanding of art and provides an interdisciplinary gain. According to the findings of the curriculum in the study, as a technical; question-answer technique, as a method; problem solving and discussion method was used.As a result; The importance of aesthetics in contemporary art is examined.Key Words: Aesthetic, Contemporary Art, Body, Art Education
Keywords: aesthetic; çağdaş resim sanatı; estetik contemporary art; Fine arts education; Güzel sanatlar eğitimi